Echocardiography and Coronary CT Angiography Imaging of Variations in Coronary Anatomy and Coronary Abnormalities in Athletic Children: Detection of Coronary Abnormalities that Create a Risk for Sudden Death. Issue 2 (21st November 2012) - Attili, Anil; Hensley, Allison K.; Jones, Fredrick D.; Grabham, Jason; DiSessa, Thomas G.
<x xml:space="preserve">Abstract</x> In a recent publication, Maron et al. reported the causes of sudden death in athletes from data collected in the US National Registry of Sudden Death in Athletes at the Minneapolis Heart Institute Registry. It is not surprising that in this study, cardiovascular disease is reported as the most common cause of sudden death in athletes (56%). The most frequently encountered cardiac pathology was hypertrophic cardiomyopathy (36% of the population who died of cardiac disease). Coronary artery anomalies of wrong sinus origin were next in frequency (17%). Less common causes attributed to coronary pathology were Kawasaki disease, origin of the left coronary artery from the pulmonary artery, atherosclerotic coronary artery disease, and myocardial bridging of the left anterior descending artery. Echocardiographic imaging along with color and pulsed‐wave Doppler has been widely employed to visualize the anatomy and function of the heart and proves to be a valuable instrument in the identification of coronary artery abnormalities. Moreover, coronary CT angiography provides additional confirmatory information. This article will discuss the scope, importance, and implications of echocardiographic and coronary CT angiography imaging of the major coronary anomalies and abnormalities in young athletes who are at risk of sudden death and who otherwise have a structurally normal heart.